2018
DOI: 10.33590/emj/10312205
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nicotinamide Adenine Dinucleotide in the Pathogenesis of Rheumatoid Arthritis: Potential Implications for Treatment

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic, inflammatory, autoimmune disease characterised by small joint swelling, deformity, and dysfunction. Its exact aetiology is unclear. Current treatment approaches do not control harmful autoimmune attacks or prevent irreversible damage without considerable side effects. Nicotinamide adenine dinucleotide (NAD+), an important hydrogen carrier in mitochondrial respiration and oxidative phosphorylation, is the major determinant of redox state in the cell. NAD+ metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In favor of this, we found that the mean IL-37 level was varied greatly in both RA patients and normal individuals among different studies. This ranged from as low as (28.83 ng/l in RA and 11.84 in the controls) in one study 44 to as high as (712.40 ng/l in RA and 133.50 in the controls) in another study, 37 2) Some elements of the DAS 28 scoring system such as the number of tender and swelling joints and the overall health condition of the patients are largely subjected to personal judgement of the physicians which might affect the calculation of DAS28 score, 3) Differences in cohorts is another possibility, so a larger cohort might explore more positive correlation, 4) Most of the studies that reveled a positive correlation between IL-37 and DAS28 were carried on Asian populations (China) and only one study was reported among Arab population (Egypt). 45 Therefore, ethnicity is an important suggested factor to be considered when interpreting IL-37 results, 5) The concentration of IL-37 was observed to be significantly higher in the aspirated synovial fluid of RA patients than the circulation 45 and therefore synovial IL-37 might be a better marker to be considered when correlated with DAS 28 score, 6) Finally, in the current study we did not take into consideration the effect of the drugs on the IL-37 level which might be considered one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 85%
“…In favor of this, we found that the mean IL-37 level was varied greatly in both RA patients and normal individuals among different studies. This ranged from as low as (28.83 ng/l in RA and 11.84 in the controls) in one study 44 to as high as (712.40 ng/l in RA and 133.50 in the controls) in another study, 37 2) Some elements of the DAS 28 scoring system such as the number of tender and swelling joints and the overall health condition of the patients are largely subjected to personal judgement of the physicians which might affect the calculation of DAS28 score, 3) Differences in cohorts is another possibility, so a larger cohort might explore more positive correlation, 4) Most of the studies that reveled a positive correlation between IL-37 and DAS28 were carried on Asian populations (China) and only one study was reported among Arab population (Egypt). 45 Therefore, ethnicity is an important suggested factor to be considered when interpreting IL-37 results, 5) The concentration of IL-37 was observed to be significantly higher in the aspirated synovial fluid of RA patients than the circulation 45 and therefore synovial IL-37 might be a better marker to be considered when correlated with DAS 28 score, 6) Finally, in the current study we did not take into consideration the effect of the drugs on the IL-37 level which might be considered one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 85%
“…Blood NAD + level is becoming an important physiological parameter for evaluating NAD + boosting strategies. Several previously reported clinical studies of NAD + supplementation established that blood NAD + content decreases with the progression of age-related diseases such as mitochondrial myopathy and rheumatoid arthritis 7,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Blood NAD + level is becoming an important physiological parameter for evaluating NAD + boosting strategies. Several previously reported clinical studies of NAD + supplementation established that blood NAD + content decreases with the progression of age-related diseases such as mitochondrial myopathy and rheumatoid arthritis 7,32 . In addition, previous studies showed that oral supplementation of NA 12 , NR 3335 or NMN 17,36 can increase the blood NAD + level and lead to beneficial outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In blood, NAD + is enriched in erythrocytes compared to serum and white blood cells (Chaleckis et al, 2014 ; Chaleckis, Murakami, Takada, Kondoh, & Yanagida, 2016 ; Clement, Wong, Poljak, Sachdev, & Braidy, 2019 ). The decline of NAD + content in blood cells (Chaleckis et al, 2016 ), muscle (Zhang et al, 2016 ), and saliva (Teruya, Goga, & Yanagida, 2021 ) has been associated with aging and age‐related symptoms such as frailty (Covarrubias et al, 2021 ; Kumar et al, 2014 ), rheumatoid arthritis (Busso et al, 2008 ; Weiqian, Caihong, & Jin, 2018 ), and heart failure (Carpenter & Dierickx, 2022 ; Yuan et al, 2022 ) at old age. In addition, oral administration of NAD + precursors as a potential intervention strategy of age‐related symptoms has been demonstrated in clinical trials to improve body NAD + levels (Chini et al, 2018 ; Imai et al, 2000 ; Khan et al, 2014 ; Pirinen et al, 2020 ; Rajman et al, 2018 ; Yoshino, Baur, & Imai, 2018 ), muscle functions, and skeletal muscle insulin sensitivity and signaling (Goody & Henry, 2018 ; Yoshino et al, 2021 ), establishing NAD + level as an emerging indicator of healthy aging.…”
mentioning
confidence: 99%